Truth, hope, compassion in a time of corona virus and a presidential election. Issue 3 (22nd June 2020) - Childs, James M.
Abstract: Despite signs of public unity in response to the COVID‐19 pandemic, the pandemic has also highlighted our divisions, disparities, and racism. The churches can have a voice for greater harmony and community if their public theology flows from their core beliefs and practices and is marked by engagement with truth, and a vision of hope acted out with compassion.